Cybersecurity : protecting critical infrastructures from cyber attack and cyber warfare - Johnson,Thomas A,Ed (CRC Press, 2015)
The World Economic Forum regards the threat of cyber attack as one of the top five global risks confronting nations of the world today. Cyber attacks are increasingly targeting the core functions of the economies in nations throughout the world. The threat to attack critical infrastructures, disrupt critical services, and induce a wide range of damage is becoming more difficult to defend against. Cybersecurity: Protecting Critical Infrastructures from Cyber Attack and Cyber Warfare examines the current cyber threat landscape and discusses the strategies being used by governments and corporations.